Методика дослідження змін деформації русел рік Прикарпатського регіону - Шевчук, В. (Видавництво Національного університету «Львівська політехніка», 2009)
Очерчено основные причины и факторы,которые влияют на изменения и деформации русел рек,сделано обзор литературы,которая касается решения гидрологических заданий рек Прикарпатского региона, предложена методика исследований деформации новейших методов получения проработки аэрокосмической и наземной информации. Outlined principal reasons and factors which influence on changing and deformations of river- beds of the rivers, the review of literature which touches the decision of hydrological tasks year of the Prykarpattya region is done, the method of researches of deformation of river-beds of the rivers is offered on the basis of the newest methods of receipt and working of aerospace and surface information.